APPLICATION OF STAD TYPE COOPERATIVE LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES ELEMENTARY SCHOOL STUDENTS - Nizami Nizami (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research is motivated by the low student mathematics learning outcomes in SDN 1 Talang Mandi. The low student learning outcomes due to a lack of optimal student ability to understand the material. This can be seen from the many mistakes students make in pretest questions given by the teacher. This study aims to improve mathematics learning outcomes of fourth-grade students at SD Negeri 1 Talang Mandi by applying the STAD type cooperative learning model. This type of research is a Class Action Research conducted in 2 cycles with stages, namely planning, implementation, observation, and reflection. The results showed that, in the first cycle, the students' absorption rate was 58.1 with enough categories. In the second cycle increased to 62.3 with a good category. Classical student mastery learning in cycle I was 58% (less) and increased in cycle II by 94% (very good). From these results, it can be concluded that the application of the STAD type cooperative learning model can improve student mathematics learning outcomes at SDN 1 Talang Mandi.